Using DIC techniques to measure strain ranges inside the cyclic plastic zone ahead of a fatigue crack tip - Giancarlo Luis Gmez Gonzles; Julin Andrs Ortz Gonzlez; Jaime Tupiass Pinho de Castro; Jos Luiz de Frana Freire. (Fracture and Structural Integrity)
A stereo microscope coupled to a 3-D Digital Image Correlation system is used to measure strain ranges on the cyclic plastic zone ahead of a fatigue crack-tip. First, a very refined speckle pattern is applied on the surface of a disk-shaped compact tension specimen of 1020 low-C steel by spraying toner powder over a layer of white paint, a suitable technique to produce the very small dots needed to map surface strain loops on that small region. This technique can achieve enough resolution to measure elastoplastic strain ranges ?e near the crack tip, which cause damage accumulation inside the cyclic plastic zone as the crack grows. The applied technique can identify as well the effects of other nonlinear phenomena that happen in the near-tip region, such as crack closure. Therefore, such measurements can be used to verify the validity of the hypotheses behind the main fatigue crack growth models.